2010
DOI: 10.1504/ijde.2010.032820
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary design using grammatical evolution and shape grammars: designing a shelter

Abstract: Publication informationInternational Journal of Design Engineering, 3 (1): 4-24 Publisher Inderscience EnterprisesLink to online version http://dx. Martin Hemberg is a post-doctoral researcher at the Department of Ophthalmology at Children's Hospital Boston. He obtained is PhD from Imperial College London and he has also worked at the Architectural Association in London. His primary research interests include matheEvolutionary design using grammatical evolution and shape grammars 3 matical and computational mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…This study is a continuation of our previous work that primarily focused on the aesthetic qualities of conceptual design [2]. Through the use of design grammars and an interactive fitness function we have shown that Grammatical Evolution (GE) [3] is capable of creating surprising and innovative designs.…”
Section: Introductionmentioning
confidence: 86%
“…This study is a continuation of our previous work that primarily focused on the aesthetic qualities of conceptual design [2]. Through the use of design grammars and an interactive fitness function we have shown that Grammatical Evolution (GE) [3] is capable of creating surprising and innovative designs.…”
Section: Introductionmentioning
confidence: 86%
“…Recent developments in computer science that use grammatical evolution [18][19][20] extend the repertoire of generative design strategies with an evolutionary approach using a reduced representation even for complex design cases. These systems build on the rule-based approach in shape grammar [21], but encompass the potential to drive the unfolding of computational designs based on behavioural systems in botom-up processes.…”
Section: Evolution In Designmentioning
confidence: 99%
“…Hart allowed the user to specify which type of mutation (and mutation rate) to apply because of the assumption that users sometimes have an intuition about what type of change is required to an individual [6]. The purpose of defining nodal and structural operators stems from our study of interactive design evolution [13]. During this study it was found that the user applied the mutation operator to explore areas of the design space that had produced interesting aesthetic designs.…”
Section: Related Researchmentioning
confidence: 99%